Outdoor thermal comfort benchmarks and optimization design for children in open parks of hot summer and cold winter region - Hu Luyao; Lu Ling; Li Xinkai; Dai Junfeng (Scientific Reports)
Abstract This study investigates the thermal comfort characteristics of children in open parks in China’s hot summer and cold winter regions, using Zizhou Park in Guilin as a case study. Through meteorological measurements and surveys, the study assesses children’s thermal perceptions across different seasons. The Universal Thermal Climate Index (UTCI) is used to evaluate the thermal environment, and the surface temperatures of various materials in the park are measured to analyze their impact on children’s thermal comfort and safety. The results indicate that children’s perception of the thermal environment significantly differs from that of adults, with a higher sensitivity to temperature fluctuations, particularly under extreme climate conditions. Based on the research data, this study proposes thermal comfort benchmarks for children, covering key factors such as temperature, humidity, and wind speed, and suggests three optimization strategies: (1) adjusting plant configurations and the layout of artificial facilities according to the specific climate characteristics of Guilin, particularly enhancing shading effects in the summer; (2) using low-temperature absorbing materials to reduce the negative impact of solar radiation on children’s thermal comfort; (3) improving the structural design of activity spaces to enhance ventilation, ensuring children’s thermal comfort across different seasons. The study provides landscape designers and urban planners with thermal comfort benchmarks and optimization design solutions for children’s activity spaces, aiming to create safer and more comfortable outdoor environments for children in hot summer and cold winter regions.